Beyond al-Qaeda: Part 2, The Outer Rings of the Terrorist Universe - Rabasa, Angel; Chalk, Peter; Cragin, Kim; Daly, Sara A.; Gregg, Heather S. (RAND Corporation, 2023)
Examines violent terrorist groups that, while not formally allied with al-Qaeda, could pose a threat to Americans now or in the future and to the security of our friends and allies. The authors show how terrorists use criminal organizations and connections to finance their activities, and they identify distinct strategies to neutralize or mitigate these threats.